Harcèlement sexuel dans l'édition : “ouvrir les yeux sur cette violence” - Gary, Nicolas (ActuaLitté, 2017)
La "culture du silence", selon l'expression consacrée, prendrait-elle fin ? Le témoignage des actrices qui ont précipité la chute du producteur américain Harvey Weinstein, entraînant une libération - une libéralisation ? - de la parole. Logiquement, ce sont les réseaux sociaux qui s'en sont fait l'écho, amplifiant les messages de colère, tristesse ou de soulagement. #MeToo, autant que le plus virulent #BalanceTonPorc, ont marqué profondément, jaillissant de toutes parts, et dénonçant le harcèlement sexuel vécu sous toutes ses formes. Alors, dans l'édition ?
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; europe; femmes* autrices; france; inégalités; périodes historiques; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; travail; violences; violences sexistes et sexuelles

Credibility Excess and the Social Imaginary in Cases of Sexual Assault - Yap, Audrey S (Feminist Philosophy Quarterly, 2017)
This paper will connect literature on epistemic injustice with literature on victims and perpetrators, to argue that in addition to considering the credibility deficit suffered by many victims, we should also consider the credibility excess accorded to many perpetrators. Epistemic injustice, as discussed by Miranda Fricker, considers ways in which someone might be wronged in their capacity as a knower. Testimonial injustice occurs when there is a credibility deficit as a result of identity-prejudicial stereotypes. However, criticisms of Fricker have pointed out that credibility is part of a more complex system that includes both deficits and excesses. I will use these points to argue that we should look closer at sources of credibility excess in cases of sexual assault. This means that in addition to considering sources of victim blaming by looking at ways in which “ideal” victims are constructed, we also need to consider ways in which “ideal” perpetrators are constructed.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem9000; injustices testimoniales; injustices épistémiques; inégalités; philosophie; philosophie féministe; privilèges; racisme; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; violences sexistes et sexuelles; éxcès de crédibilité